An Evaluation of Continuing Education Programme in Puducherry - Reddy, P. Adinarayana; Devi, D. Uma; Reddy, E. Mahadeva (JOURNAL OF INDIAN EDUCATION, 2011)
The Continuing Education Programme was launched in Puducherry under the aegis of National Literacy Mission to create facilities for retention of literacy and application of functional literacy for improving living standards, to disseminate the developmental information, to create awareness on national concerns, to promote employable skills and to create learning environment through establishing libraries and reading rooms, cultural and recreational activities. The present paper deals with assessment of the performance of the Continuing Education Programme in terms of physical and infrastructural components created and quality of delivery of programme components. The findings provide an insight to the programme administrators about the status of the programme and steps to be taken to improve its quality of delivery mechanism and also provides suggestions.